(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this research, the powder mixing technology has been used to control the ratio of added, where the addition of tin oxide to the bismuth oxide of by (1,3,5,7)% by using vacuum evaporation method. The range of thickness for thin films (40-100)nm . EDX analysis shows the results of the ratios were close to the required values. XRD analysis shows pure bismuth oxide crystalline of the tetragonal phase (β-Bi2O3), observed that the structural properties improves with addition (1)% and the composition of a triangular compound (Bi64SnO98), and with addition (5)% we have a new triple compound (Bi12SnO20). By increasing the impurities, the structural properties become close from random, the tin oxide begins with bismuth oxide separation. AFM measurement shows the thin films surface a pekes like (nano needle) and the grain size rises to (20.2-22 nm). In the case of increased impurities, the surface becomes smooth, and the nano needle decrease with grain size . The optical properties showed a rise in the value of the optical power gap (2.6-3)eV and directly allowed transitions are simply increasing from (3.3-3.5) eV, and directly forbidden transitions are simply increasing to from (2.48-2.73) eV.